Combination of 1064 nm QS Nd:YAG Photoacoustic Technology and Exosome for Facial Rejuvenation - Setiawan, Stanley; Putranto, Samuel Septrian; Linata, Angela Maria; Salim, Stephanie; Mertosono, Novia Sari Andriati; Nobel, Shelly; Wardianti, Flora Asri; Anggraini, Ita; Rahmawati, Zulaikha Rizqina (UI Scholars Hub, 2025)
Background: Facial rejuvenation has become a global trend in cosmetic and aesthetic dermatology to restore youthful skin. The combination of 1064 nm Q-Switched Neodymium:Yttrium Aluminum Garnet (QS Nd:YAG) laser and exosomes as a facial rejuvenation procedure restores youthfulness by increasing collagen and elastin. Case Illustration: This case series evaluated the effectiveness of 1064 nm QS Nd:YAG laser with and without human amniotic fluid stem cell-derived exosomes (hAFSC-exo) for facial rejuvenation in six adults aged 24–39 years with Fitzpatrick skin types III-IV. Participants were randomized to receive either laser treatment alone or combined with intradermal hAFSC-exo injections every two weeks for three sessions, with outcomes assessed through blinded objective and subjective evaluations. Objective assessments using a skin analyzer showed improvements for both groups, with consistently greater improvement in the combination therapy group. Meanwhile, subjective evaluations using the GAIS scale indicated that combination therapy recipients experienced “very much improved” outcomes, minimal side effects, and good overall tolerance. Discussion: Facial rejuvenation using 1064 nm QS Nd:YAG laser and hAFSC-exo was evaluated in this case series. Both treatments improved skin quality, but combination therapy demonstrated superior results. However, improvements in pigmentation were limited, and subjective assessments may have been influenced by response bias. The short follow-up period limited the evaluation of long-term skin changes; extended studies are warranted to assess sustained outcomes. Conclusion: Combination therapy of 1064 nm QS Nd:YAG laser and exosomes has a favorable result for facial rejuvenation.